Optimizing the Application of Diversion by the PPA Unit in Handling Children in Conflict with the Law to Achieve Restorative Justice - Putri Dewa, Dinan (Advances in Police Science Research Journal, 2024)
One of the commitments of the Indonesian National Police Chief is to prioritize prevention, restrorative justice, and problem solving. The application of diversion in the settlement of child cases aims to realize retrorative justice. The application of diversion by PPA Unit of Pemalang Police in resolving child cases is not optimal. The purpose of this study is to describe the stages of management and originalization resources for implementing diversion by PPA Unit in resolving child cases at the Pemalang Police. The theory used is the grand theory of Management Theory, middle theory consists of management stages and organizatonal resources, as well as applied theory which consists of competency theory, law enforcement theory, and SWOT theory. This research is a qualitative research with a case study approach which is carried out by interviews, observations, document studies and FGD with informants in Pemalang. The results of this study indicate the applicaton of diversion by PPA Unit in handling children in conflict with law in order to reduce the number of child cases that are continued to prosecution were not fully adequate and in accordance. Therefore, Chief of Pemalang Police Criminal Investigation Unit as the subject of this final project needs to take steps to solve the problem.